1984
DOI: 10.1021/jo00182a011
|View full text |Cite
|
Sign up to set email alerts
|

Halogen regiochemistry and substituent stereochemistry determination in marine monoterpenes by carbon-13 NMR

Abstract: The use of 13C NMR shifts in defining halogen regiochemistry or six-membered ring substituent stereochemistry in marine monoterpenes is considered in detail. New additivity parameters and model compound 13C NMR shift data are presented. Structures are proposed for three new red seaweed monoterpenes (3, 4, and 5), and revisions are suggested for four other published structures (6, 7, 8, and 9). Our approach can be extended to certain marine sesquiterpenes such as the chamigrane class. Comparisons between calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 0 publications
2
52
0
Order By: Relevance
“…10 Furthermore, the bromine-bearing methine carbon was considered to be C6 because of its reasonable chemical shift (d C 51.8, d H 4.70). 11,12 Thus, the gross structure of nakiterpiosin was determined to be as shown in Figure 1.…”
Section: Isolation Of Nakiterpiosin and Nakiterpiosinonementioning
confidence: 99%
“…10 Furthermore, the bromine-bearing methine carbon was considered to be C6 because of its reasonable chemical shift (d C 51.8, d H 4.70). 11,12 Thus, the gross structure of nakiterpiosin was determined to be as shown in Figure 1.…”
Section: Isolation Of Nakiterpiosin and Nakiterpiosinonementioning
confidence: 99%
“…The 13 C NMR chemical shifts of the quaternary carbon at δ 135.0 and the methylene at δ 51.2 are consistent with an olefinic chlorine substituent and a chloromethylene, respectively. 9 A NOESY correlation between H-1 and CH 3 -10 confirmed the E-geometry for the C-2/C-3 double bond, while correlations from H-5 to CH 3 -9 and CH 3 -10 are consistent with Z-and E-geometries for the C-4/C-5 and C-6/C-7 double bonds, respectively.…”
Section: Resultsmentioning
confidence: 62%
“…9 This was confirmed by the molecular formula of C 17 H 16 NOF 5 Cl 2 Br (m/z 493.9713) obtained from the HRESIMS spectrum of the PFBO-oxime of 3 (8).…”
Section: Resultsmentioning
confidence: 64%
“…22) The negative optical rotation of 2, together with the characteristic chemical shifts of the methyl carbon, C-9 at d 25.1 (CDCl 3 ), indicated that 2 should be an erythro derivative (expected values for erythro and threo series are d C 25 and d C 28, respectively). 29) Thus, 2 was identified as (5E,7E)-3,4-erythro-3,4,8-trichloro-7-dichloromethyl-3-methylocta-1,5,7-triene, which was previously reported from the Pacific red alga Plocamium cartilagineum. 22) Compounds 1 and 2 were evaluated for cytotoxicity against a panel of five human solid tumor cell lines and showed mild to significant activity (Table 2).…”
Section: Resultsmentioning
confidence: 74%